Unraveling the anti-inflammatory effects of Mediterranean diet in patients with cancer remission - Di Tolla, Michele Francesco; Libutti, Michele; D’Onofrio, Giovanna; Riccio, Alessandra; Cabaro, Serena; Longo, Michele; Parascandolo, Alessia; Ferraro, Giusy; Formisano, Elia; D’Esposito, Vittoria; Formisano, Pietro (Frontiers in Immunology, 2025)
IntroductionCancer survivors display impaired quality of life and increased risk to develop cardiometabolic comorbidities. Low-grade chronic inflammation (LGCI) plays a crucial role in cancer progression and in cardiometabolic diseases. Although the Mediterranean Diet is widely recognized for its beneficial effects on body composition and systemic inflammation, direct evidence of its impact on cancer survivors remains limited. This study aimed to explore the associations between inflammatory biomarkers, metabolic status, and Mediterranean diet adherence, evaluating the effectiveness of a personalized dietary intervention.MethodsA total of 132 patients with cancer remission were enrolled; anamnestic, anthropometric, bioimpedential, clinical, and nutritional data were collected. Serum concentrations of cytokines, chemokines, growth factors, and metabolic markers were measured at baseline and at a six-month follow-up.ResultsBaseline analysis revealed distinct clusters linking inflammatory status, clinical variables, and metabolic profiles, confirming associations between systemic inflammation and body composition features, without clear separation among cancer types. After dietary intervention, a significant reduction in specific inflammatory and metabolic biomarkers was observed, with distinct effects depending on tumor type. For instance, Leptin and Insulin levels decreased, particularly in Breast cancer patients, whereas Colorectal cancer patients exhibited a reduction in pro-inflammatory cytokines such as IL-1β, IL-6, IL-8, and TNF-α, even in the absence of weight loss and bioimpedential feature changes. Retrospective analysis further highlighted that nutritionally modified molecules were associated with metabolic and inflammatory risk factors at baseline.DiscussionDespite the lack of a control group and the high attrition rate may represent limitations for this observational pilot study, we have provided evidence that nutritional intervention could be a promising complementary strategy in oncological management by modulating key inflammatory and metabolic pathways involved in tumor pathophysiology and comorbidities.